2001
DOI: 10.1002/hed.1044
|View full text |Cite
|
Sign up to set email alerts
|

Organ preservation with radiotherapy for T1‐T2 carcinoma of the pyriform sinus

Abstract: RT alone or combined with a planned neck dissection resulted in local control with larynx preservation in a high proportion of patients. The chance of cure is comparable to that observed after conservation surgery, and the risk of major complications is lower. The addition of adjuvant chemotherapy is unlikely to improve the probability of organ preservation, but might improve locoregional control for patients with advanced nodal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…Amdur et al 22,25 reported on 101 patients with T1/2 pyriform sinus carcinoma treated with radiotherapy to the primary and post-radiotherapy neck dissection. Actuarial local control was 90% for T1 and 80% for T2 lesions, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Amdur et al 22,25 reported on 101 patients with T1/2 pyriform sinus carcinoma treated with radiotherapy to the primary and post-radiotherapy neck dissection. Actuarial local control was 90% for T1 and 80% for T2 lesions, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…We believe that to achieve such results, surgical technique must be precise to guarantee preservation of the superior laryngeal nerve in this open-field surgical approach. Such functional outcomes should be compared with much higher rates of permanent tracheotomy and gastrostomy when using, on the one hand, hyperfractionated radiotherapy 22,25 or, on the other hand, supraglottic 16 or supracricoid hemilaryngopharyngectomy. 17,18 Because the incidence of pyriform sinus carcinoma is rare, large adequately powered studies to compare treatment regimens have not been performed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, local control rates with RT for PPW carcinomas are reported to be 36% at 5 years 7. However, the 5-year overall survival for stage IV-B disease is just 5% after RT alone 8.…”
Section: Discussionmentioning
confidence: 99%
“…In einer nachfolgenden Publikation aus derselben Institution wurde die 5-Jahresrate f ü r die lokale Tumorkontrolle mit 90 % f ü r T1-und 80 % f ü r T2-Karzinome angegeben. Die lokale Kontrolle mit Organerhalt betrug f ü r Patienten mit T1-Karzinomen 86 % und f ü r Patienten mit T2-Karzinomen 82 %[256] . Garden et al[222] konnten bei 57 T1-und T2-Karzinomen in 75,5 % der F ä lle den Tumor lokal beherrschen.…”
unclassified